PENDIDIKAN PEMAKAI (USER EDUCATION) DAN PEMANFAATAN PERPUSTAKAAN (STUDI KASUS DI PERPUSTAKAAN UIN SUSKA RIAU) - Muhammad Tawaf; Khaidir Alimin (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2011)
Education Program user (user education) at the library of the State Islamic University of Sultan Sharif Kasim Riau is a program implemented during New Student Orientation (OMB). Education users (user education) is necessary to evaluate, especially on one educational outcome user (user education) is use of the library. Formulation of the problem in this study were : (1) How is the implementation of user education at the library of UIN Suska? (2) The extent to which the influence of education on the use of UIN Suska Library library in Riau? This study user linear regression to quantify the influence of user education programs (user education) on the use of the library by students UIN Suska Riau. Questionnaires distributed to 100 students who have attended educational programs the user (user education) in the library UIN Suska Riau. From the results of questionnaires are processed with SPSS, the results of the regression equation as follows: Y = 62.085 + 0.417 X + e. Constants for 62.085 states that if the user is in a constant state of education (fixed) then the impact on the utilization of the library of 62.085 units. The results of user education coefficient (X) indicates at 0.417. This means if the user education increased 100 percent, then the positive effect or an increase of 41.70 percent utilization of the library. Next, calculate the t-test = 2.460 larger two-tail t table at a significant level at 5% level at 1.9845 or (t-hits = 2.460> t-table = 1.945). Therefore rejected and Ho = Ha = acceptable. Thus it can be concluded that the educational programs the user (user education) are held in the Library UIN SUSKA Riau significantly influence use of the library.